2020
DOI: 10.1186/s12882-020-02051-w
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum sodium levels predict poor clinical outcomes in patients with insomnia

Abstract: Background: The association between lower serum sodium levels and the clinical outcomes of insomnia patients remains unclear. We explored whether lower serum sodium is associated with poor clinical outcomes in patients with insomnia. Methods: We retrospectively enrolled patients with a diagnosis of insomnia from January 2011 to December 2012. We divided participants into three groups according to initial serum sodium level: tertile 1 (< 138 mmol/L), tertile 2 (138.0-140.9 mmol/L), and tertile 3 (≥ 141.0 mmol/L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…If only the data on serum sodium and AKI onset are considered, the findings are everything but consistent. Two studies revealed a role of hyponatremia in AKI onset prediction (18,25), four studies did not confirm the observations [ 17 , 20 , 26 , 28 ]. The article by Peres at al [ 17 ] included ICU treated individuals (n = 152), recruited from a single ICU, dysnatremia was not AKI predictive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If only the data on serum sodium and AKI onset are considered, the findings are everything but consistent. Two studies revealed a role of hyponatremia in AKI onset prediction (18,25), four studies did not confirm the observations [ 17 , 20 , 26 , 28 ]. The article by Peres at al [ 17 ] included ICU treated individuals (n = 152), recruited from a single ICU, dysnatremia was not AKI predictive.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with insomnia were analyzed by Bae et al [ 20 ]. The term insomnia has been well defined: it must be suspected if at least one “nocturnal sleep symptom” and a daytime or “waking symptom” occur, both attributable to impaired sleep at night [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…That said, there is limited evidence that increased energy intake or changes in the consumption of polyunsaturated fats influences variability in sleep per se [52]. There is, however, some research which does suggest that salt (which links chloride and sodium) can negatively influence sleep via increased blood pressure and fluid retention [68,69] in either direction (i.e., very low salt and very high salt diets). As such, further examinations of the relationship between salt and sleep are warranted to further examine directionality.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in BP due to the high plasma level of sodium can also be explained by the disability of the kidneys to excrete salt and the compensatory response required to restore the balance of sodium [ 6 ]. It was previously shown that among patients with insomnia, lower levels of sodium are associated with poor clinical outcomes [ 7 ]. In addition, there is a possibility of the activation of the autonomic nervous system in patients with insomnia, which could also be associated with both lower levels of serum sodium and increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%